FAKTOR PREDIKTOR LUARAN DISABILITAS PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT BETHESDA YOGYAKARTA - Irene Gracia Wijayanti,* Rizaldy Taslim Pinzon,* Esdras Ardi Pramudita* (NEURONA, 2019)
INTRODUCTION IT IS ESTIMATED THAT AROUND 25 TO 74 OF THE 50 MILLION STROKE PATIENTS WHO LIVE BECOME INDEPENDENT EITHER NEED THE FULL OR PARTIAL ASSISTANCE DUE TO DECREASED PHYSICAL ABILITIES COGNITION AND EMOTIONS